Pergulatan Tradisi, Agama, Negara: Analisis Sosio-Kultural Keturunan Tionghoa dan Perkembangan Gereja Tionghoa Indonesia (1950-1999) - Cipta, Samudra Eka (LP4MK STKIP PGRI Lubuklinggau, 2021)
During the Dutch East Indies there were several Chinese-Christian communities characterized by the existence of the Chinese church. The Liberal Democratic period of Chinese-Christian development is experiencing rapid development. The developments are supported by government policies regarding religious identity issues for the people of descent. After the fall of democracy guided by the birth of the New Order, the development of the Chinese-Christians increased sharply. The politics that the new Order period is ' ' political assimilation ' ' by trying to remove cultural elements in a particular society. This is marked by the new Order government policy that prohibits the practice of Confucian teaching on Chinese descent as a form of propaganda in Chinese communism. During the new order Mas Chinese descent did a massive religious conversion. Another impact for the people of descent is the name change by the name of Indonesian people in general. This research gave birth to problem formulation of 1) how early social development of Chinese descent society?, 2) How the Indonesian Chinese community response to the government policy of time Sukarno and Suharto?, 3) How is the effort of reconciliation in the effort to preserve the values of culture and philosophy for the Society of Chinese descent?.